Managing Self-Improvement Activities for Primary School Teachers: A Solution - Dung, Nguyen Tri (Technium Social Sciences Journal, 2023)
The article presents a novel solution to effectively manage self-improvement activities for primary school teachers, addressing the need for personalized professional development in the education sector. Acknowledging the crucial role of teachers in shaping students' futures, the proposed solution aims to enhance their skills, knowledge, and pedagogical approaches to ensure optimal learning outcomes. To ensure the effectiveness of the solution, the authors emphasize the importance of ongoing assessment and feedback mechanisms. Regular evaluations help measure the impact of the self-improvement activities, providing valuable insights for further refinement. Additionally, teachers are encouraged to reflect on their progress and share their experiences, facilitating a collective learning process.